Dampak Kualitas Produk dan Pelayanan Terhadap Loyalitas: Studi pada Pelanggan Sami Petshop Abiansemal - Kesuma Suryawan, Tjokorda Gde Agung Wijaya; Meryawan, I Wayan; Budi Utama, Gede Wira (Universitas Ngurah Rai, 2023)
Customer loyalty is characterized by repetitive purchasing actions towards the same product and location to fulfill specific needs or desires. The success in achieving this goal is influenced by various factors, including product quality and service quality. In the effort to enhance customer loyalty, attention to issues related to product and service quality becomes essential. Therefore, this research focuses on examining the impact of product quality and service quality on customer loyalty at Sami Petshop in Abiansemal. The objectives of this study encompass two aspects: to determine the partial influence of product quality and service quality on customer loyalty at Sami Petshop, Kecamatan Abiansemal, Kabupaten Badung, and to assess the simultaneous impact of product quality and service quality on customer loyalty at Sami Petshop, Kecamatan Abiansemal, Kabupaten Badung. The sample size of 57 respondents was determined using purposive sampling technique. Data analysis involved classic assumption tests, multiple linear regression analysis, determination analysis, partial significance tests (t-test), and simultaneous significance tests (F-test). The research results indicate a positive and significant influence, both partially and simultaneously, of product quality and service quality on customer loyalty at Sami Petshop, Kecamatan Abiansemal, Kabupaten Badung. The implications of this research extend to the field of marketing management, providing a deeper understanding of the key factors influencing customer loyalty. The insights gained can assist marketing practitioners in developing more effective strategies, optimizing customer experiences, and enhancing customer retention, ultimately contributing to the growth and sustainability of the business.